2013
DOI: 10.1002/ejlt.201200256
|View full text |Cite
|
Sign up to set email alerts
|

Potential protective effect of Nigella sativa crude oils towards fatty liver in rats

Abstract: The main purpose of the present research was to study the protective effect of Nigella sativa crude oils (NCO) extracted from plain and g-irradiated seeds towards inflammatory fatty liver (steatohepatitis). The protective effect of the oils was tested during induction of inflammatory fatty liver in rats through feeding high fructose diet. Biochemical analyses including plasma lipids, tumor necrosis factor-a (TNF-a) and malondialdehyde (MDA) levels and liver fat and liver function tests were carried out to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 78 publications
4
16
0
Order By: Relevance
“…Nigella sativa oil showed previously to produce a hepatoprotective effect in rats (Al-Suhaimi, 2012) which was confirmed by the work of Al-Okbi et al (2013), who reported its protective effect against steatohepatitis. This effect was ascribed to the volatile oil fraction, particularly thymoquinone and p-cymene and to a lesser extent to the fatty acid profile of Nigella crude oil.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Nigella sativa oil showed previously to produce a hepatoprotective effect in rats (Al-Suhaimi, 2012) which was confirmed by the work of Al-Okbi et al (2013), who reported its protective effect against steatohepatitis. This effect was ascribed to the volatile oil fraction, particularly thymoquinone and p-cymene and to a lesser extent to the fatty acid profile of Nigella crude oil.…”
Section: Discussionmentioning
confidence: 65%
“…Rats with MHRS showed a significant elevation in all liver fat with dyslipidemia which may be due to feeding high fructose as described by Kawasaki et al (2009) andAl-Okbi et al (2013). Nigella sativa oil showed previously to produce a hepatoprotective effect in rats (Al-Suhaimi, 2012) which was confirmed by the work of Al-Okbi et al (2013), who reported its protective effect against steatohepatitis.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations